OPTIMIZING THE FOCUS OF CLASS 1 STUDENTS' LEARNING ON THE SUBJECT OF AQIDAH AKHLAK THROUGH THE DEMONSTRATION METHOD - Nisa Amini, Putri Hoyrun; Azizah Azzahro, Putri Nur; Fadillah, Rizki; Farida, Nur Aini; Makbul, M (Journal Analytica Islamica, 2024)
Class I PAI subjects in Madrasah Ibtidaiyah (MI) Bahrul Ulum Karawang became the subject of Classroom Action Research (CAR). These problems include monotonous learning atmosphere, students who are not enthusiastic to follow the lessons, students who are not conducive, and students who do not concentrate in class. This happens because lectures are still the primary way of teaching. The demonstration learning method is the increase we chose. Class I students of Madrasah Ibtidaiyah (MI) Bahrul Ulum Karawang, which totaling 30 people, is the subject of this research. Data collection techniques used include teaching practices, interviews, and observations. This classroom action research was conducted in two cycles. The results show that (1) the application of the demonstration learning model in Islamic religious education subjects has a positive impact on student learning. (2) Madrasah Ibtidaiyah (MI) Bahrul Ulum Karawang was seen from the percentage increase in cycle I of 50%, then increased in cycle II of 88.89%. This indicator can be seen from the increase in student learning outcomes after implementing the Demonstration learning model. Students are increasingly enthusiastic and eager to participate in learning Islamic Religious Education. Teachers and students have better educational interactions. The application of the demonstration technique in this research was considered successful in improving student learning outcomes.